Ground-based millimeter-wave spectrometer versus UARS microwave limb sounder version 5 retrievals of stratospheric HNO3 over Antarctica - Muscari, G.; Santee, M.; Zafra, R. L. de (2004)
We present the first intercomparison between the two longest records of gas-phase HNO3 vertical profiles in the Antarctic stratosphere.